2010
DOI: 10.1016/j.econedurev.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, comparative advantage, and return to education: The case of Taiwan

Abstract: By considering heterogeneity in abilities and self-selection in educational choice, this paper adopts the heterogeneous human capital model to estimate rate of return to university education using data from the 1990 and 2000 Taiwan's Manpower Utilization Surveys. The Taiwan empirical study shows that significant heterogeneous return to education does exist, and that the educational choice was made according to the principle of comparative advantage. The estimated rates of return for attaining university were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This would provide the labour market less space and time to absorb the extra college graduates produced. Using data from 1990 to 2000 in Taiwan, Chuang and Lai ( 2010 ) suggested that the trend of declining return to university education may have been caused by the rapid expansion of the number of colleges and universities and the increasing supply of college graduates in the 1990s. Gindling and Sun ( 2002 ) confi rmed that the decrease in the wages of workers with higher education, as compared to non-degree holders, is attributable to the increased number of students enrolled in universities and junior colleges in the 1990s.…”
Section: Discussion: Mixed Messages Regarding Changing Wagesmentioning
confidence: 99%
“…This would provide the labour market less space and time to absorb the extra college graduates produced. Using data from 1990 to 2000 in Taiwan, Chuang and Lai ( 2010 ) suggested that the trend of declining return to university education may have been caused by the rapid expansion of the number of colleges and universities and the increasing supply of college graduates in the 1990s. Gindling and Sun ( 2002 ) confi rmed that the decrease in the wages of workers with higher education, as compared to non-degree holders, is attributable to the increased number of students enrolled in universities and junior colleges in the 1990s.…”
Section: Discussion: Mixed Messages Regarding Changing Wagesmentioning
confidence: 99%
“…College and university graduates suffer the most, followed by senior high school and junior college leavers. Using data from 1990 to 2000 in Taiwan, Chuang and Lai (2010) suggested that the trend of declining return to university education may have been caused by the rapid expansion of the number of colleges and universities and the increasing supply of college graduates in the 1990s. Gindling and Sun (2002) confirmed that the decrease in the wages of workers with higher education, compared with non-degree holders, is attributable to the increased number of students enrolled in universities and junior colleges in the 1990s.…”
Section: Features Of Massification: In Pursuit Of Higher Degreesmentioning
confidence: 99%
“…Our proposed method is applicable to empirical studies that identify and estimate marginal treatment effects and/or policy relevant treatment effects. Examples include, but are not limited to, Auld (2005), Basu, Heckman, Navarro-Lozano, andUrzua (2007), Doyle Jr. (2008), Moffitt (2008), Chuang and Lai (2010), Carneiro, Heckman, and Vytlacil (2011), Galasso, Schankerman, and Serrano (2013, Basu, Jena, Goldman, Philipson, and Dubois (2014), Belskaya, Peter, and Posso (2014), Johar and Maruya (2014), Lindquist and Santavirta (2014), Moffitt (2014), Dobbie and Song (2015), Joensen and Nielsen (2016), Kasahara, Liang, andRodrigue (2016), Carneiro, Lokshin, andUmapathi (2017), Cornelissen, Dustmann, (2018), Felfe andLalive (2018), andKamhöfer, Schmitz, andWestphal (2018).…”
Section: Introductionmentioning
confidence: 99%